Gender-Responsive Digital Deep Learning Management in Indonesian Vocational Schools - Junaina; Jahani; Tulus Suryanto; Koderi; Syafrimen Syafril (Women, Education, and Social Welfare, 2026)
Digital transformation in vocational high schools should not be evaluated only through infrastructure availability, but also through its capacity to deepen learning, protect student well-being, and widen equitable school-to-work opportunities. This study evaluates the management of digital-based deep learning in four public vocational high schools in Pesawaran Regency, Indonesia, using a qualitative document-evaluation design. The data corpus comprised 2025 Education Report Cards, school vision and mission statements, school profiles, annual work plans, principal work programs, and follow-up planning documents from SMKN 1 Gedong Tataan, SMKN 1 Tegineneng, SMKN 1 Negeri Katon, and SMKN Padang Cermin. The documents were analyzed through thematic synthesis informed by open-systems theory, CIPP evaluation, continuous quality improvement, TPACK, project-based vocational pedagogy, and a gender-responsive welfare lens. The findings show that the schools have strong strategic commitments to character formation, digital learning, industry partnership, project learning, and vocational relevance. However, the Education Report Cards reveal an important management paradox: ICT facilities were consistently strong, while resource allocation for quality improvement remained weak and instructional quality was unstable in several schools. The study proposes a PPEPP-CIPP model for gender-responsive digital deep learning management, linking standard setting, implementation, evaluation, control, and improvement with context, input, process, and product evidence. The model positions digital learning as a human-centered and welfare-sensitive strategy for improving vocational learning quality, student participation, and transition readiness.